ml2171
Answered

At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

Solve: 3n - 6 = -8(6 +5n)
and explain how to solve it


Sagot :

Answer:

Step-by-step explanation:

First use distributive property: a(b + c) = a*b + a*c

3n - 6 = -8(6 + 5n)

3n - 6 = 6 * (-8) + 5n *(-8)

3n - 6 = -48 - 40n

Now add 40n to both sides

3n - 6 + 40n = -48 - 40n + 40n

43n - 6 = -48

Now add 6 to both sides

43n - 6 + 6 = -48 + 6

           43n = -42

               n = -42 /43

Answer:

0.98

Step-by-step explanation:

3n-6=-8(6+5n)

3n-6=-48-40n

3n=-48-40n+6

40n+3n=-42

43n=-42

n=0.98 (I rounded it)

We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.